Structural and biochemical insights of xylose MFS and SWEET transporters in microbial cell factories: challenges to lignocellulosic hydrolysates fermentation - Taveira, Iasmin Cartaxo; Carraro, Cláudia Batista; Nogueira, Karoline Maria Vieira; Pereira, Lucas Matheus Soares; Bueno, João Gabriel Ribeiro; Fiamenghi, Mateus Bernabe; dos Santos, Leandro Vieira; Silva, Roberto N. (Frontiers in Microbiology, 2024)
The production of bioethanol from lignocellulosic biomass requires the efficient conversion of glucose and xylose to ethanol, a process that depends on the ability of microorganisms to internalize these sugars. Although glucose transporters exist in several species, xylose transporters are less common.Several types of transporters have been identified in diverse microorganisms, including members of the Major Facilitator Superfamily (MFS) and Sugars Will Eventually be Exported Transporter (SWEET) families. Considering that Saccharomyces cerevisiae lacks an effective xylose transport system, engineered yeast strains capable of efficiently consuming this sugar are critical for obtaining high ethanol yields. This article reviews the structure-function relationship of sugar transporters from the MFS and SWEET families. It provides information on several tools and approaches used to identify and characterize them to optimize xylose consumption and, consequently, second-generation ethanol production.